2015
DOI: 10.1093/cercor/bhv102
|View full text |Cite
|
Sign up to set email alerts
|

Brain Events Underlying Episodic Memory Changes in Aging: A Longitudinal Investigation of Structural and Functional Connectivity

Abstract: Episodic memories are established and maintained by close interplay between hippocampus and other cortical regions, but degradation of a fronto-striatal network has been suggested to be a driving force of memory decline in aging. We wanted to directly address how changes in hippocampal-cortical versus striatal-cortical networks over time impact episodic memory with age. We followed 119 healthy participants (20-83 years) for 3.5 years with repeated tests of episodic verbal memory and magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 102 publications
9
97
2
Order By: Relevance
“…In addition, we found a correlation between the episodic memory measure of list learning with the left volume of the hippocampus across all subjects, suggesting evidence for this impairment to be reflected in the volumetric structure of the hippocampus, which is similarly supported by other studies [79, 80]. There was also a relationship between cognitive impairment in several episodic memory measures and worse gray matter subcortical integrity in both the caudate and hippocampus, also providing support for microstructural abnormalities in these structures to be related to cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found a correlation between the episodic memory measure of list learning with the left volume of the hippocampus across all subjects, suggesting evidence for this impairment to be reflected in the volumetric structure of the hippocampus, which is similarly supported by other studies [79, 80]. There was also a relationship between cognitive impairment in several episodic memory measures and worse gray matter subcortical integrity in both the caudate and hippocampus, also providing support for microstructural abnormalities in these structures to be related to cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…The right cingulum angular bundle runs along the inferior cingulum and connects frontal to hippocampal and para-hippocampal regions (Schmahmann et al 2007). Given that chronic cannabis use is associated with worsening verbal memory (Solowij and Battisti 2008;Broyd et al 2015), and poorer integrity of the cingulum angular bundle is also associated with poorer memory in both younger and older adults (Fjell et al 2015;Ezzati et al 2015), our findings may provide further evidence for impairment in the memory systems of chronic cannabis users.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies showed that several striatal subregions (especially caudate) and the hippocampus interact during episodic memory (41)(42)(43)(44)(45)(46), and considerable overlap has been observed in the pattern of functional connectivity for hippocampal and caudate seeds (47). This suggests that these regions are part of a shared functional network.…”
Section: Discussionmentioning
confidence: 94%